Effectiveness of Intervention Based Art Therapy (AT) Module on Aggressive Behaviour Among Delinquent Adolescents - U-Seman, Nurul Atiqah Binti Che; Chethiyar, Saralah Devi Mariamdaran (South Asian Journal of Social Sciences and Humanities, 2021)
For youngsters, verbal communication is tough, and for aggressive children, it is even more challenging. Art therapy was used as a successful intervention in this study to reduce aggressive behaviour among delinquent adolescents aged 13 to 18 years. The current study used a Qusai experimental (pretest-posttest) research design. Adolescents (n=30) were randomly assigned to a control group and an experimental group. For ten weeks, the management was carried out once a week. The Nelson and Finch (2000) children inventory of anger was used to assess anger at the start and conclusion of a 10-week period. When linked to the control group, the art therapy group exhibited a substantial reduction in anger (p.001). These findings suggest that art therapy can help aggressive children to minimize their anger and expand their behaviour. Art therapy, which combines natural elements of art with notions of mental methodslike cognitive-behavioral therapy, could be a significant involvement, particularly for adolescents.